Kajian Intertekstual Novel Dilan Karya Pidi Baiq dengan Novel Milea Karya Pidi Baiq - Ani Marliana; Idawati Sintiawati; Mimin Sahmini (IKIP Siliwangi, 2018)
Literary works are the media used by the author in conveying ideas, experiences to be conveyed to the reader. In addition, literary works can also be found in the intertextual relationship between one literary work with other literary works. The purpose of this study is to know how the intertextual relationship between the novel